Hubungan Kadar Hemoglobin dan Paritas Dengan Lama Persalinan Kala II - Kadek Renata Antrini; Idah Ayu Wulandari; Ni Komang Sri Ariani; Luh Komang Suwarma Santi (WOMB Midwifery Journal, 2025)
Hemoglobin (Hb) plays a crucial role in maintaining the stamina of mothers during childbirth, particularly in stage II, which requires strength for pushing. Anemia in pregnant women can prolong the labor process due to a lack of energy for pushing. This study aims to determine the relationship between Hb levels and parity with the duration of stage II labor. This cross-sectional study involved 42 respondents and was analyzed using the Spearman rank test. The results indicate a positive correlation between Hb levels and the duration of stage II labor (r = 0.416; p = 0.006), as well as a negative correlation between parity and the duration of stage II labor (r = -0.705; p = 0.000). These findings suggest that higher Hb levels tend to shorten the duration of stage II labor, while lower parity tends to prolong it.